Estimation of Plant Growth Promoting Potential of Two Nickel Accumulating Morphotypes Isolated from River Hooghly on Indian Yellow Mustard (Brassica hirta) - Mukherjee, Tanoy; Ghosh, Avijit; Maitra, Santanu (International Journal of Applied Sciences and Biotechnology, 2014)
Plant growth promoting bacteria (PGPB) are known to influence plant growth by various direct or indirect mechanisms. Present study was conducted with an aim to estimate the PGPB potential of two nickel tolerant bacterial isolates from river Hooghly. Isolates (I-3) (Gram negative coccobacilli) and (II-1) (Gram positive rods) were observed, among a total of 22 other isolates, to tolerate and accumulate significant amounts of nickel and also have multiple Plant Growth Promoting (PGP) activities like IAA production and phosphate solubilization. Present study also shows that seeds of yellow mustard (Brassica hirta) inoculated with both the test isolates individually, significantly enhanced root and shoot growth and also protected the plant from the various phytotoxic effects of nickel.DOI: http://dx.doi.org/10.3126/ijasbt.v2i4.11107 Int J Appl Sci Biotechnol, Vol. 2(4): 413-419